Optical film, image display panel, and image display device

By designing an optical film concave and convex surface that meets specific ISO standards and building an anti-glare layer and an anti-reflective layer on it, the problem of the optical film that the dark feeling and abrasion resistance decrease after increasing the surface concave and convexity is achieved, and the influence of reflected scattered light is suppressed while achieving high anti-glare and abrasion resistance.

CN118625429BActive Publication Date: 2025-04-25DAI NIPPON PRINTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410847055.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-04-27
Filing Date
2023-04-25
Publication Date
2025-04-25
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

After the existing optical film increases the surface concave and convexity, the black feeling of the black display part of the image is reduced and the abrasion resistance is also reduced, and the prior art has not effectively studied these problems.

Method used

An optical film is designed with a concave and convex surface in accordance with the provisions of ISO 25178-2:2012. Specifically, the volume of the protruding peak portion is 0.010 ml/m2 or more and 0.050 ml/m2 or less, and the minimum autocorrelation length Sal is 4.0 μm or more and 12.0 μm or less. The optical film has a functional layer on the substrate, and the surface of the functional layer is the concave and convex surface, and includes an anti-glare layer and an anti-reflection layer.

Benefits of technology

While maintaining high anti-glare and scratch resistance, it is possible to suppress the reduction of the darkness caused by reflected scattered light, ensuring high quality of image display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118625429B_ABST
    Figure CN118625429B_ABST
Patent Text Reader

Abstract

The present invention provides an optical film, an image display panel and an image display device. An optical film, wherein the optical film has a concavo-convex surface, and the protruding peak solid volume Vmp specified by ISO 25178-2:2012 is 0.010 ml / m 2 Above and 0.050ml / m 2 Hereinafter, the minimum autocorrelation length Sal prescribed by ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese invention patent application with an application date of April 25, 2023, an invention name of “Optical film, image display panel and image display device” and an application number of 202380014714.5 (PCT / JP2023 / 016223). Technical Field

[0002] The present disclosure relates to an optical film, an image display panel, and an image display device. Background Art

[0003] An optical film having a concavo-convex surface may be provided on the surface of an image display device such as a television, a notebook PC, or a desktop PC monitor in order to suppress reflection of background such as lighting or people.

[0004] As an optical film having a concavoconvex surface, for example, Patent Documents 1 and 2 have been proposed.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. WO 2019 / 026466

[0008] Patent Document 2: International Publication No. WO 2019 / 026471 Summary of the invention

[0009] Problems to be solved by the invention

[0010] Conventional optical films can provide a predetermined anti-glare property by increasing the surface unevenness of the optical film. However, for optical films with increased surface unevenness, there is a case where the pitch-black feeling of the black display part of the image is reduced due to reflected scattered light. In addition, for optical films with increased surface unevenness, there is a case where the scratch resistance is reduced.

[0011] The optical films of Patent Documents 1 and 2 do not study at all the reduction of the black feeling due to reflected scattered light and the scratch resistance.

[0012] An object of the present disclosure is to provide an optical film that has excellent anti-glare properties, can suppress reduction in blackness due to reflected scattered light, and has good scratch resistance.

[0013] Means for solving problems

[0014] The present disclosure provides the following optical films, image display panels, and display devices [1] to [2].

[0015] [1] An optical film having a concavo-convex surface, wherein the concavo-convex surface has a protruding peak solid volume Vmp specified in ISO 25178-2:2012 of 0.010 ml / m 2 Above and 0.050ml / m 2 Hereinafter, the minimum autocorrelation length Sal specified in ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.

[0016] [2] An image display panel, wherein the image display panel is arranged on a display element in such a manner that the surface of the concave-convex surface side of the optical film described in [1] faces the side opposite to the display element, and the optical film is arranged on the outermost surface.

[0017] [3] An image display device, comprising the image display panel described in [2].

[0018] Effects of the Invention

[0019] The optical film, image display panel, and image display device disclosed herein are excellent in anti-glare properties, can suppress reduction in blackness due to reflected scattered light, and can provide good scratch resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic cross-sectional view showing one embodiment of the optical film of the present disclosure.

[0021] Figure 2 is a cross-sectional view showing one embodiment of the image display panel of the present disclosure. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present disclosure will be described.

[0023] [Optical film]

[0024] The optical film of the present disclosure has a concavoconvex surface, and regarding the concavoconvex surface, the protruding peak solid volume Vmp specified by ISO 25178-2:2012 is 0.010 ml / m 2 Above and 0.050ml / m 2 Hereinafter, the minimum autocorrelation length Sal prescribed by ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.

[0025] Figure 1 2 is a schematic cross-sectional view of the cross-sectional shape of the optical film 100 of the present disclosure.

[0026] Figure 1The optical film 100 has a concavoconvex surface. Figure 1 The optical film 100 has a functional layer 20 on a substrate 10, and the surface of the functional layer 20 becomes the concavoconvex surface of the optical film. Figure 1 The functional layer 20 includes an anti-glare layer 21 and an anti-reflection layer 22 .

[0027] Figure 1 That is, the scale of each layer constituting the optical film 100 and the scale of the concavo-convex surface are schematically shown for ease of illustration and are different from the actual scale. Figure 2 Same.

[0028] The optical film of the present disclosure is not limited to the following as long as the Vmp and Sal of the concavo-convex surface are within the prescribed range. Figure 1 For example, the optical film may be a single-layer structure of an anti-glare layer, may be a two-layer structure of a substrate and an anti-glare layer, and may have functional layers other than the anti-glare layer and the anti-reflection layer.

[0029] A preferred embodiment of the optical film is: a functional layer is provided on a substrate, and the surface of the functional layer is the concavo-convex surface. A more preferred embodiment of the optical film is: an anti-glare layer is included as the functional layer, and the surface of the anti-glare layer is the concavo-convex surface. A further preferred embodiment of the optical film is: an anti-glare layer and an anti-reflection layer are included as the functional layer, and the surface of the anti-reflection layer is the concavo-convex surface.

[0030] <Concave and convex surface>

[0031] The optical film needs to have a concavoconvex surface.

[0032] In addition, the concavo-convex surface of the optical film needs to be: the protruding peak volume Vmp specified by ISO 25178-2:2012 is 0.010 ml / m 2 Above and 0.050ml / m 2 Hereinafter, the minimum autocorrelation length Sal prescribed by ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.

[0033] Vmp is a parameter indicating the volume of a protruding portion that is higher than the core. The core is equivalent to a portion having an average height in a concave-convex surface. The larger the Vmp, the larger the volume of the portion protruding from the core. Even for a concave-convex surface with the same "arithmetic mean height Sa" described later, there is a tendency that the higher the height of the portion protruding from the core, the larger the Vmp of the concave-convex surface.

[0034] In this specification, a “portion protruding from the core portion” may be referred to as a “protruding convex portion”.

[0035] In this specification, Vmp and Vvc described later are calculated by setting the load area ratio for separating the core and the protruding peak to 10% and the load area ratio for separating the core and the protruding valley to 80%. That is, in this specification, "Vmp" means "the solid volume of the protruding peak when the load area ratio for separating the core and the protruding peak is 10%", and "Vvc" means "the space volume of the core when the load area ratio for separating the core and the protruding valley is 80%".

[0036] Sal is a parameter that focuses on the lateral direction. The smaller Sal is, the more the concavo-convex surface has a shape with dense concavo-convexity, and the larger Sal is, the more the concavo-convex surface has a shape with wide intervals between concavo-convexity. For the value of "average length RSm of roughness curve elements" specified by JIS B0601, fine concavo-convexity has almost no effect, and only large concavo-convexity will have an effect. On the other hand, for the value of Sal, not only large concavo-convexity but also fine concavo-convexity will have an effect, which is different from RSm. In addition, even if the intervals between concavo-convexity are wider, if the convex portion is smaller or the concavo-convex shape is more complicated, Sal also tends to become smaller. In addition, if the convex portion is a monotonous shape, there is a tendency for Sal to become larger.

[0037] When Vmp is less than 0.010ml / m 2 In the case of Vmp less than 0.010 ml / m 2 On the other hand, when Vmp is 0.010 ml / m 2 In the above case, the reflected scattered light on the concavo-convex surface can be suppressed, so the black feeling can be improved. 2 In the above case, the anti-glare property can be easily improved.

[0038] Even if Vmp is 0.010ml / m 2 However, when Sal exceeds 12.0 μm, it is impossible to achieve a good black feeling.

[0039] It can be considered that Vmp is 0.010ml / m 2 The uneven surface having the above-mentioned Sal of 12.0 μm can provide a good black feeling due to the effects of x1 to x4 described below.

[0040] As a premise, a case where the optical film of the present disclosure is provided on an image display device is considered.

[0041] x1: Light is incident on the concavo-convex surface. Hereinafter, the light incident on the concavo-convex surface is sometimes referred to as incident light. Also, the direction in which the light is incident on the concavo-convex surface is sometimes referred to as the first direction. Also, the direction opposite to the first direction is sometimes referred to as the second direction. There is an observer in the second direction.

[0042] x2: A portion of the incident light is reflected on the concavoconvex surface.

[0043] x3: A portion of the reflected light reflected on the concavo-convex surface collides with the convex portion of the concavo-convex surface. The larger Vmp is and the smaller Sal is, the more the proportion of the reflected light colliding with the convex portion of the concavo-convex surface increases. On the other hand, the smaller Vmp is and the larger Sal is, the more the proportion of the reflected light colliding with the convex portion of the concavo-convex surface decreases.

[0044] x4: A portion of the reflected light that collides with the convex portion is repeatedly totally reflected in the convex portion and travels toward the image display device side. The light that travels to the image display device side is absorbed by the image display device and is not recognized as reflected scattered light by the observer. Therefore, a concave-convex surface with a large Vmp and a small Sal can suppress reflected scattered light and make the pitch-black feeling good.

[0045] When Vmp exceeds 0.050ml / m 2 In the case of Vmp exceeding 0.050ml / m, it means that the volume of the protruding convex part is large. The part of the concave-convex surface that is damaged by the friction object is mainly near the convex part, especially the convex part with a higher height is easy to be damaged. Therefore, when Vmp exceeds 0.050ml / m 2 In the case of , the scratch resistance of the uneven surface cannot be improved.

[0046] In addition, even when Vmp is 0.050ml / m 2 If the Sal is less than 4.0 μm, the scratch resistance cannot be improved. The part of the concavo-convex surface that is damaged by the friction object is mainly near the convex part. When the Sal is less than 4.0 μm, the number of convex parts on the concavo-convex surface increases, so it is easy to damage the concavo-convex surface. Therefore, even if Vmp is 0.050 ml / m 2 However, when Sal is less than 4.0 μm, the scratch resistance cannot be improved.

[0047] The lower limit of Vmp is preferably 0.020 ml / m 2 More preferably 0.025 ml / m 2 More preferably, 0.030 ml / m 2 The upper limit of Vmp is preferably 0.040 ml / m 2 Below, more preferably 0.035 ml / m 2 the following.

[0048] As an embodiment of the range of Vmp, 0.010 ml / m 2 Above and 0.050ml / m 2 Below, 0.010ml / m 2 Above and 0.040ml / m 2 Below, 0.010ml / m 2 Above and 0.035ml / m 2 Below, 0.020ml / m 2 Above and 0.050ml / m 2 Below, 0.020ml / m 2 Above and 0.040ml / m 2 Below, 0.020ml / m 2 Above and 0.035ml / m 2 Below, 0.025ml / m 2 Above and 0.050ml / m 2 Below, 0.025ml / m 2 Above and 0.040ml / m 2 Below, 0.025ml / m 2 Above and 0.035ml / m 2 Below, 0.030ml / m 2 Above and 0.050ml / m 2 Below, 0.030ml / m 2 Above and 0.040ml / m 2 Below, 0.030ml / m 2 Above and 0.035ml / m 2 the following.

[0049] The lower limit of Sal is preferably 5.0 μm or more, more preferably 6.0 μm or more, further preferably 6.5 μm or more, further preferably 7.0 μm or more. The upper limit of Sal is preferably 11.0 μm or less, more preferably 10.5 μm or less, further preferably 10.0 μm or less.

[0050] As embodiments of the range of Sal, 4.0 μm to 12.0 μm, 4.0 μm to 11.0 μm, 4.0 μm to 10.5 μm, 4.0 μm to 10.0 μm, 5.0 μm to 12.0 μm, 5.0 μm to 11.0 μm, 5.0 μm to 10.5 μm, 5.0 μm to 10.0 μm, 6.0 μm to 12.0 μm, 6.0 μm to 10.5 μm and below 11.0μm, 6.0μm and below 10.5μm, 6.0μm and below 10.0μm, 6.5μm and below 12.0μm, 6.5μm and above 11.0μm, 6.5μm and below 10.5μm, 6.5μm and below 10.0μm, 7.0μm and above 12.0μm, 7.0μm and below 11.0μm, 7.0μm and below 10.5μm, 7.0μm and above 10.0μm.

[0051] Vmp and Sal, as well as Vvc, Sxp, and Sa described later, are measured using a confocal laser microscope. Examples of confocal laser microscopes include the "VK-X" series from KEYENCE. In addition, Vmp, Sal, Sxp, and Sa can be easily calculated by using the "multi-file analysis application" of the "VK-X" series described above.

[0052] The measurement conditions for measuring Vmp, Sal, Sxp and Sa using the aforementioned "VK-X" series are preferably in accordance with the conditions described in the embodiments. For example, the F-operation is preferably set to plane tilt correction (region designation). In addition, with respect to the measurement area, it is preferred that one side is 50 μm to 200 μm, and with respect to the measurement points, it is preferred that there are more than 500 points and less than 2000 points on each side.

[0053] The optical film disclosed in the present invention preferably has a core space volume Vvc of 0.30 ml / m 2 Above and 1.00ml / m 2 Vvc is a parameter indicating the volume of the space of the core. The core can be roughly said to be the volume of water accumulated in the concavities and convexities forming the core of the concavity and convexity surface when water is dropped onto the concavity and convexity surface.

[0054] By setting Vvc to 0.30ml / m 2 By setting Vvc to 1.00 ml / m 2 The following can easily improve the scratch resistance.

[0055] The lower limit of Vvc is preferably 0.35 ml / m 2 More preferably 0.40 ml / m 2 More preferably, 0.50 ml / m 2 The upper limit of Vvc is preferably 0.90 ml / m 2 Below, more preferably 0.80ml / m 2 Below, more preferably 0.70 ml / m 2 Below, more preferably 0.65 ml / m 2 the following.

[0056] As an embodiment of the range of Vvc, 0.30 ml / m 2 Above and 1.00ml / m 2 Below, 0.30ml / m 2 Above and 0.90ml / m 2 Below, 0.30ml / m 2 Above and 0.80ml / m 2 Below, 0.30ml / m 2 Above and 0.70ml / m 2 Below, 0.30ml / m 2 Above and 0.65ml / m 2 Below, 0.35ml / m 2 Above and 1.00ml / m 2 Below, 0.35ml / m 2 Above and 0.90ml / m 2 Below, 0.35ml / m 2 Above and 0.80ml / m 2 Below, 0.35ml / m 2 Above and 0.70ml / m 2 Below, 0.35ml / m 2 Above and 0.65ml / m 2 Below, 0.40ml / m 2 Above and 1.00ml / m 2 Below, 0.40ml / m 2 Above and 0.90ml / m 2 Below, 0.40ml / m 2 Above and 0.80ml / m 2 Below, 0.40ml / m 2 Above and 0.70ml / m 2 Below, 0.40ml / m 2 Above and 0.65ml / m 2 Below, 0.50ml / m 2Above and 1.00ml / m 2 Below, 0.50ml / m 2 Above and 0.90ml / m 2 Below, 0.50ml / m 2 Above and 0.80ml / m 2 Below, 0.50ml / m 2 Above and 0.70ml / m 2 Below, 0.50ml / m 2 Above and 0.65ml / m 2 the following.

[0057] Regarding the optical film disclosed in the present invention, it is preferred that the peak height Sxp of the concavo-convex surface specified by ISO 25178-2:2012 is greater than 0.55 μm and less than 2.00 μm. Sxp is a parameter representing the difference between the average surface of the concavo-convex surface and the convex portion after removing particularly high convex portions in the concavo-convex surface. The lower limit of Sxp is preferably greater than 0.65 μm, more preferably greater than 0.80 μm, and further preferably greater than 0.90 μm. The upper limit of Sxp is preferably less than 1.75 μm, more preferably less than 1.60 μm, further preferably less than 1.35 μm, and further preferably less than 1.20 μm.

[0058] By setting Sxp to 0.55 μm or more, the anti-glare property can be easily improved, and by setting Sxp to 2.00 μm or less, the scratch resistance can be easily improved.

[0059] Regarding the implementation of the range of Sxp, it is possible to list 0.55 μm to 2.00 μm, 0.55 μm to 1.75 μm, 0.55 μm to 1.60 μm, 0.55 μm to 1.35 μm, 0.55 μm to 1.20 μm, 0.65 μm to 2.00 μm, 0.65 μm to 1.75 μm, 0.65 μm to 1.60 μm, 0.65 μm to 1.35 μm, 0.65 μm to 1. And 1.20μm or less, 0.80μm or more and 2.00μm or less, 0.80μm or more and 1.75μm or less, 0.80μm or more and 1.60μm or less, 0.80μm or more and 1.35μm or less, 0.80μm or more and 1.20μm or less, 0.90μm or more and 2.00μm or less, 0.90μm or more and 1.75μm or less, 0.90μm or more and 1.60μm or less, 0.90μm or more and 1.35μm or less, 0.90μm or more and 1.20μm or less.

[0060] In this specification, Sxp means the difference between the height at which the load area ratio is 2.5% and the height at which the load area ratio is 50%.

[0061] Regarding the optical film disclosed in the present invention, it is preferred that the arithmetic mean height Sa of the concavoconvex surface specified by ISO 25178-2:2012 is 0.20 μm or more and 1.00 μm or less. The lower limit of Sa is preferably 0.25 μm or more, more preferably 0.30 μm or more, and further preferably 0.32 μm or more. The upper limit of Sa is preferably 0.80 μm or less, more preferably 0.60 μm or less, and further preferably 0.40 μm or less.

[0062] By setting Sa to 0.20 μm or more, the anti-glare property can be easily improved, and by setting Sa to 1.00 μm or less, the scratch resistance can be easily improved.

[0063] Regarding the implementation of the range of Sa, there can be listed 0.20 μm to 1.00 μm, 0.20 μm to 0.80 μm, 0.20 μm to 0.60 μm, 0.20 μm to 0.40 μm, 0.25 μm to 1.00 μm, 0.25 μm to 0.80 μm, 0.25 μm to 0.60 μm, 0.25 μm to 0.40μm or less, 0.30μm or more and 1.00μm or less, 0.30μm or more and 0.80μm or less, 0.30μm or more and 0.60μm or less, 0.30μm or more and 0.40μm or less, 0.32μm or more and 1.00μm or less, 0.32μm or more and 0.80μm or less, 0.32μm or more and 0.60μm or less, 0.32μm or more and 0.40μm or less.

[0064] In this specification, unless otherwise specified, the surface shape (Vmp, Sal, Vvc, Sxp, and Sa) and optical properties (haze, total light transmittance, etc.) refer to the average value of the measured values ​​at 16 locations.

[0065] In this specification, regarding the 16 measurement locations, an area 1 cm from the outer edge of the measurement sample is removed as a blank, and for the remaining area, 16 intersections when lines dividing the longitudinal and transverse directions into 5 equal parts are drawn as the center of the measurement. For example, in the case where the measurement sample is a rectangle, an area 0.5 cm from the outer edge of the rectangle is removed as a blank, and the 16 intersections of the imaginary lines dividing the remaining area into 5 equal parts in the longitudinal and transverse directions are measured as the center, and the parameters are calculated using the average value. In the case where the measurement sample is a shape other than a rectangle, such as a circle, an ellipse, a triangle, or a pentagon, it is sufficient to draw a rectangle inscribed in these shapes and perform 16 measurements on the rectangle using the above method.

[0066] In this specification, unless otherwise specified, the surface shape (Vmp, Sal, Vvc, Sxp, and Sa) and optical properties (haze, total light transmittance, etc.) are values ​​measured under the conditions of a temperature of 23±5°C and a relative humidity of 40% to 65%. In addition, before each measurement, the target sample is exposed to the atmosphere for 30 minutes to 60 minutes, and then the measurement is performed.

[0067] <Base material>

[0068] In order to facilitate the production of the optical film and the handling properties of the optical film, the optical film preferably has a substrate.

[0069] As the substrate, it is preferred to have light transmittance, smoothness, heat resistance, and excellent mechanical strength. Such substrates include plastic films such as polyester, triacetyl cellulose (TAC), cellulose diacetate, cellulose acetate butyrate, polyamide, polyimide, polyether sulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, polymethyl methacrylate, polycarbonate, polyurethane, and amorphous olefin (Cyclo-Olefin-Polymer: COP). The substrate may also be formed by laminating two or more plastic films together.

[0070] Among plastic films, polyester films processed by stretching are preferred for mechanical strength and dimensional stability, and polyester films processed by biaxial stretching are more preferred. Polyethylene terephthalate films, polyethylene naphthalate films, etc. can be cited as polyester films. TAC films and acrylic films are preferred because they are easy to make light transmittance and optical isotropy good. COP films and polyester films are preferred because they are excellent in weather resistance.

[0071] The thickness of the substrate is preferably 5 μm or more and 300 μm or less, more preferably 20 μm or more and 200 μm or less, and further preferably 30 μm or more and 120 μm or less.

[0072] When the optical film is to be thinned, the upper limit of the thickness of the substrate is preferably 100 μm or less, and the more preferred upper limit is 80 μm or less. In addition, when the substrate is a low moisture permeability substrate such as polyester, COP, acrylic acid, the upper limit of the thickness of the substrate used for thinning is preferably 60 μm or less, and the more preferred upper limit is 40 μm or less. Even in the case of a large screen, if the upper limit of the thickness of the substrate is the above range, it is also preferred in that deformation can be difficult to occur.

[0073] The thickness of the substrate can be measured, for example, using a film thickness measuring instrument. Examples of film thickness measuring instruments include a digital display standard external micrometer (model: MDC-25SX) from Mitutoyo. The thickness of the substrate can be measured by measuring any 10 points at the average value above.

[0074] Regarding the substrate, the total light transmittance of JIS K7361-1:1997 is preferably 70% or more, more preferably 80% or more, and even more preferably 85% or more.

[0075] The substrate has a haze of preferably 10% or less, more preferably 5% or less, and further preferably 3% or less in accordance with JIS K7136:2000.

[0076] In order to improve the adhesiveness, the surface of the substrate may be subjected to a physical treatment such as a corona discharge treatment, or a chemical treatment. In addition, the substrate may have an easy-adhesion layer on the surface.

[0077] <Functional layer>

[0078] The optical film preferably has a functional layer on the substrate, and the surface of the functional layer is the concavoconvex surface. Examples of the functional layer include an anti-glare layer, an anti-reflection layer, an antistatic layer, and an antifouling layer.

[0079] The optical film preferably includes an antiglare layer as a functional layer, and the surface of the antiglare layer is the concavoconvex surface. The optical film further preferably includes an antiglare layer and an antireflection layer as functional layers, and the surface of the antireflection layer is the concavoconvex surface.

[0080] Anti-glare layer

[0081] The anti-glare layer is a layer that plays a central role in anti-glare properties.

[0082] The anti-glare layer can be formed, for example, by (A) a method using an embossing roll, (B) etching treatment, (C) molding by a mold, (D) coating film formation by coating, etc. Among these methods, molding by a mold (C) is preferred in order to easily obtain a stable surface shape, and coating film formation by coating (D) is preferred in order to improve productivity and cope with a variety of products.

[0083] In the method of (C), for example, the anti-glare layer can be formed by allowing the resin to flow into a mold and taking the molded resin out of the mold. For the mold, a mold in which the surface shape of the anti-glare layer is inverted is used. Such a mold can be made, for example, by the following methods (c1-1) to (c1-2) or the following method (c2).

[0084] (c1-1) A shape in which Vmp and Sal are within a predetermined range is created by simulation. Then, the simulated shape is inverted.

[0085] (c1-2) A mold is obtained by engraving metal using a laser so that the inverted shape is reflected.

[0086] (c2) A mold in which the shape of the anti-glare layer produced in (D) is reversed is obtained by a general electroforming method.

[0087] When the anti-glare layer is formed by (D), for example, the following methods (d1) and (d2) can be used. (d1) is preferred because the ranges of Vmp and Sal can be adjusted more easily than (d2).

[0088] (d1) A method of applying and drying a coating liquid containing a binder resin and particles to form an anti-glare layer having unevenness due to the particles.

[0089] (d2) A method of forming projections and depressions by applying a coating liquid containing an arbitrary resin and a resin having poor compatibility with the aforementioned resin and causing the resin to phase separate.

[0090] -thickness-

[0091] In order to achieve a balance between curl suppression, mechanical strength, hardness, and toughness, the thickness T of the antiglare layer is preferably 2.0 μm to 10.0 μm, more preferably 3.0 μm to 8.0 μm, and further preferably 4.0 μm to 6.0 μm.

[0092] The thickness of the anti-glare layer can be calculated by, for example, selecting any 20 locations on a cross-sectional photograph of an optical film obtained using a scanning transmission electron microscope and calculating the average value thereof. Preferably, the accelerating voltage of the STEM is 10 kV or more and 30 kV or less, and the magnification of the STEM is 1000 or more and 7000 or less.

[0093] -Element-

[0094] The anti-glare layer preferably mainly comprises a resin component. Furthermore, the anti-glare layer preferably comprises, as required, organic particles and inorganic particles, nanometer-sized particles, refractive index adjusters, antistatic agents, antifouling agents, ultraviolet absorbers, light stabilizers, antioxidants, viscosity adjusters, and additives such as thermal polymerization initiators.

[0095] The antiglare layer preferably contains a binder resin and particles.

[0096] As for particles, organic particles and inorganic particles can be listed, preferably inorganic particles. That is, the anti-glare layer preferably contains a binder resin and inorganic particles. In addition, the anti-glare layer more preferably contains a binder resin, inorganic particles and organic particles.

[0097] - Particles -

[0098] Examples of the inorganic particles include silica, alumina, zirconia, and titania, and silica is preferred. Among the inorganic particles, amorphous inorganic particles are also preferred, and amorphous silica is more preferred.

[0099] Examples of the organic particles include particles containing one or more resins selected from polymethyl methacrylate, polyacrylic acid-styrene copolymers, melamine resins, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensates, silicones, fluorine-based resins, and polyester-based resins.

[0100] The particles preferably do not include particles with a large aspect ratio. This is because particles with a large aspect ratio tend to protrude from the surface of the anti-glare layer, thus sometimes reducing scratch resistance. Specifically, as particles, it is preferred that the particles with an aspect ratio of more than 10 are not included, and more preferably the particles with an aspect ratio of more than 5 are not included.

[0101] Amorphous inorganic particles refer to inorganic particles having no specific shape that are obtained by pulverizing inorganic particles having a large particle size and then classifying them.

[0102] The particles preferably include inorganic particles. In addition, the particles more preferably include amorphous inorganic particles, and further preferably include amorphous inorganic particles and organic particles. The amorphous inorganic particles are preferably amorphous silica.

[0103] Amorphous inorganic particles have a tendency to increase Vmp more easily and reduce Sal more easily than spherical particles. However, if the particle size of the amorphous inorganic particles is too consistent, there is the following situation: Vmp does not become large enough, or Sal becomes too small. Therefore, with respect to amorphous inorganic particles, it is preferred that the volume-based cumulative distribution of particle size is the range described later. However, if inorganic particles are used alone, agglomeration is likely to occur. Therefore, in order to easily make Vmp and Sal the above-mentioned range, as particles, it is preferred to include amorphous inorganic particles and organic particles with a specified particle size distribution.

[0104] Regarding inorganic particles such as amorphous inorganic particles, preferably, the volume-based cumulative distribution d10 of particle size, the volume-based cumulative distribution d50 of particle size, and the volume-based cumulative distribution d90 of particle size satisfy the following relationships (1) and (2).

[0105] 1.5≤d50 / d10≤4.0 (1)

[0106] 1.0≤d90 / d50≤3.0 (2)

[0107] D50 / d10 being 1.5 or more means that the particle size distribution of the inorganic particles in the region below the average is wider. By setting d50 / d10 to more than 1.5, it is easy to give fine concavoconvexity to the concavoconvex surface, so Sal can be easily reduced. By setting d50 / d10 to less than 4.0, it is possible to suppress the amount of inorganic particles buried in the anti-glare layer from increasing, thereby improving the addition efficiency of the inorganic particles.

[0108] d90 / d50 being 1.0 or more means that the particle size distribution of the inorganic particles in the region where the particle size is above the average is wide. By setting d90 / 50 to 1.0 or more, Vmp can be easily increased and Sal can be easily increased. By setting d90 / d50 to 3.0 or less, Vmp can be easily suppressed from becoming too large and Sal from becoming too large.

[0109] The lower limit of d50 / d10 is more preferably 2.0 or more, and further preferably 2.3 or more, and the upper limit is more preferably 3.5 or less, and further preferably 3.0 or less.

[0110] The lower limit of d90 / d50 is more preferably 1.5 or more, and further preferably 1.8 or more, and the upper limit is more preferably 2.5 or less, and further preferably 2.0 or less.

[0111] The d10, d50, and d90 of inorganic particles such as amorphous inorganic particles can be measured by a laser diffraction method.

[0112] The volume-based cumulative distribution d50 of the particle size of the inorganic particles such as the amorphous inorganic particles is preferably 2.9 μm or more and 6.0 μm or less, more preferably 3.5 μm or more and 5.7 μm or less, and further preferably 4.0 μm or more and 5.5 μm or less.

[0113] By setting d50 to 2.9 μm or more, the number of inorganic particles can be prevented from excessively increasing, so that Sal can be easily prevented from becoming too small. By setting d50 to 6.0 μm or less, the number of inorganic particles can be prevented from excessively decreasing, so that Sal can be easily prevented from becoming too large.

[0114] Regarding the thickness T of the antiglare layer and d50 of inorganic particles such as amorphous inorganic particles, d50 / T is preferably 0.55 to 1.00, more preferably 0.60 to 0.95, and further preferably 0.70 to 0.90.

[0115] By setting d50 / T to be 0.55 or more, Sal can be easily increased, and by setting d50 / T to be 1.00 or less, Sal can be easily decreased.

[0116] Regarding the thickness T of the antiglare layer and d90 of inorganic particles such as amorphous inorganic particles, d90 / T is preferably 1.00 to 1.50, more preferably 1.08 to 1.45, and further preferably 1.20 to 1.40.

[0117] By setting d90 / T to be 1.00 or more, Vmp can be easily increased, and by setting d90 / T to be 1.50 or less, Vmp can be easily decreased.

[0118] The content of the inorganic particles such as amorphous inorganic particles is preferably 8 parts by mass to 40 parts by mass, more preferably 12 parts by mass to 30 parts by mass, and further preferably 15 parts by mass to 28 parts by mass, relative to 100 parts by mass of the binder resin.

[0119] By setting the content of inorganic particles such as amorphous inorganic particles to 8 parts by mass or more, it is possible to suppress an excessive decrease in the number of inorganic particles, and thus it is possible to easily suppress Sal from becoming excessively large.

[0120] By setting the content of inorganic particles such as amorphous inorganic particles to 40 parts by mass or less, it is possible to suppress an excessive increase in the number of inorganic particles, and thus it is possible to easily suppress Sal from becoming too small.

[0121] The content of the organic particles is preferably 1 to 25 parts by mass, more preferably 3 to 18 parts by mass, and further preferably 8 to 14 parts by mass, relative to 100 parts by mass of the binder resin.

[0122] By making the content of organic particles 1 part by mass or more, the aggregation of inorganic particles can be easily suppressed. In addition, by making the content of organic particles 1 part by mass or more, the number of organic particles can be suppressed from being excessively reduced, so that Vmp and Sal can be easily suppressed from becoming too large.

[0123] By making the content of organic particles less than 25 parts by mass, the number of organic particles can be suppressed from increasing excessively, so that Vmp and Sal can be easily suppressed from becoming too small. Since the particle size distribution of organic particles is relatively uniform, if the content of organic particles increases, Vmp and Sal tend to become smaller.

[0124] However, when two or more kinds of organic particles are contained and the difference between the average particle diameters of the organic particles is large, Vmp and Sal tend to become too large regardless of the content of the organic particles. Therefore, when two or more kinds of organic particles are used, the difference between the average particle diameters of the organic particles is preferably set to 1.7 μm or less, more preferably 1.0 μm or less, more preferably 0.5 μm or less, more preferably 0.2 μm or less, and more preferably 0.1 μm or less.

[0125] The average particle diameter of the organic particles is preferably 1.0 μm or more and 5.0 μm or less, more preferably 1.2 μm or more and 3.0 μm or less, and further preferably 1.3 μm or more and 2.5 μm or less.

[0126] By making the average particle size of the organic particles greater than 1.0 μm, it is possible to suppress the excessive increase in the number of organic particles, thereby easily suppressing Vmp and Sal from becoming too small. By making the average particle size of the organic particles less than 5.0 μm, it is possible to suppress the excessive decrease in the number of organic particles, thereby easily suppressing Vmp and Sal from becoming too large.

[0127] In this specification, the average particle size of organic particles refers to a value determined as a volume average value d50 in a laser diffraction method.

[0128] As for organic particles, particles with a narrow particle size distribution are preferred. Specifically, as for organic particles, the proportion of particles within the range of ±0.5 μm of the average particle diameter is preferably 80% by volume or more of the total amount of organic particles, more preferably 85% by volume or more, and further preferably 90% or more. By making the particle size distribution of inorganic particles such as amorphous inorganic particles wider and the particle size distribution of organic particles narrower, Vmp and Sal can be easily made within the above range.

[0129] Examples of the shape of the organic particles include spherical, disc-shaped, rugby-shaped, irregular, etc. Among these shapes, spherical organic particles are preferred because they can easily control the particle size distribution.

[0130] The ratio of the average particle size of the organic particles to the thickness of the anti-glare layer (the average particle size of the organic particles / the thickness of the anti-glare layer) is preferably 0.20 or more and 0.70 or less, more preferably 0.23 or more and 0.50 or less, and further preferably 0.25 or more and 0.35 or less. By making the average particle size of the organic particles / the thickness of the anti-glare layer be the aforementioned range, Vmp and Sal can be easily made into the aforementioned range.

[0131] -Inorganic particles-

[0132] The anti-glare layer may further contain inorganic fine particles in addition to the binder resin and the particles. In the present specification, the inorganic fine particles can be distinguished from the above-mentioned particles by the average particle size.

[0133] When the anti-glare layer contains inorganic fine particles, the difference between the refractive index of the particles and the refractive index of the composition of the anti-glare layer other than the particles becomes small, and the internal haze can be easily reduced.

[0134] Examples of the inorganic fine particles include fine particles made of silica, alumina, zirconia, and titania, etc. Among them, silica is also preferred because it is easy to suppress the generation of internal haze.

[0135] The average particle diameter of the inorganic fine particles is preferably 1 nm or more and 200 nm or less, more preferably 2 nm or more and 100 nm or less, and further preferably 5 nm or more and 50 nm or less.

[0136] -Binder resin-

[0137] In order to improve the scratch resistance, the binder resin preferably includes a cured product of a curable resin composition such as a cured product of a thermosetting resin composition or a cured product of an ionizing radiation curable resin composition, and more preferably includes a cured product of an ionizing radiation curable resin composition.

[0138] The binder resin may contain a thermoplastic resin within a range not impairing the effects of the present disclosure.

[0139] As the binder component, inorganic binder components such as silica matrix can be cited, but organic binder components are preferred. That is, as the binder component of the anti-glare layer of the present disclosure, a binder resin which is an organic binder component is preferred.

[0140] The ratio of the cured product of the curable resin composition to the total amount of the binder resin is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.

[0141] The thermosetting resin composition is a composition containing at least a thermosetting resin and is a resin composition that is cured by heating.

[0142] Examples of the thermosetting resin include acrylic resin, polyurethane resin, phenolic resin, urea-melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.

[0143] Ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). As the ionizing radiation curable functional group, ethylenically unsaturated bond groups such as (meth) acryloyl, vinyl, allyl, and epoxy, oxetane, etc. can be listed. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, and a compound having more than two ethylenically unsaturated bond groups is more preferred, wherein a polyfunctional (meth) acrylate compound having more than two ethylenically unsaturated bond groups is further preferred. As the polyfunctional (meth) acrylate compound, any of a monomer and an oligomer can be used.

[0144] Ionizing radiation refers to electromagnetic waves or charged particle beams that have energy quanta that can cause molecules to polymerize or cross-link. Ultraviolet light (UV) or electron beams (EB) are usually used. In addition, electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion rays may also be used.

[0145] Examples of the bifunctional (meth)acrylate monomer in the polyfunctional (meth)acrylate compound include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxy diacrylate, bisphenol A tetrapropoxy diacrylate, and 1,6-hexanediol diacrylate.

[0146] Examples of the trifunctional or higher-functional (meth)acrylate monomer include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, and isocyanuric acid-modified tri(meth)acrylate.

[0147] The (meth)acrylate monomers may be monomers in which a part of the molecular skeleton is modified. For example, monomers in which a part of the molecular skeleton is modified by ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. may be used.

[0148] Examples of the polyfunctional (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.

[0149] Urethane (meth)acrylate can be obtained by, for example, a reaction between a polyol and an organic diisocyanate and a hydroxy (meth)acrylate.

[0150] Preferred epoxy (meth)acrylates are: (meth)acrylates obtained by reacting trifunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with (meth)acrylic acid; (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with polybasic acids and (meth)acrylic acid; and (meth)acrylates obtained by reacting difunctional or higher aromatic epoxy resins, alicyclic epoxy resins, aliphatic epoxy resins, etc. with phenols and (meth)acrylic acid.

[0151] The weight average molecular weight of the polyfunctional (meth)acrylate oligomer is preferably 500 or more and 3,000 or less, and more preferably 700 or more and 2,500 or less.

[0152] In this specification, the weight average molecular weight is measured by GPC analysis, and is an average molecular weight converted into standard polystyrene.

[0153] In addition, for the purpose of adjusting the viscosity of the anti-glare layer coating solution, a monofunctional (meth)acrylate can be used as an ionizing radiation curable compound. Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate.

[0154] The ionizing radiation curable compounds may be used alone or in combination of two or more.

[0155] When the ionizing radiation curable compound is an ultraviolet curable compound, the ionizing radiation curable composition preferably contains an additive such as a photopolymerization initiator or a photopolymerization accelerator.

[0156] Examples of the photopolymerization initiator include one or more selected from acetophenone, benzophenone, α-hydroxyalkylphenone, Michler's ketone, benzoin, benzyl dimethyl ketal, benzoylbenzoate, α-acyl oxime ester, thioxanthones and the like.

[0157] The photopolymerization accelerator can reduce polymerization hindrance caused by air during curing and accelerate the curing speed. Examples of the accelerator include isopentyl p-dimethylaminobenzoate and ethyl p-dimethylaminobenzoate.

[0158] When the binder resin includes a cured product of an ionizing radiation curable resin composition, the ionizing radiation curable resin composition preferably includes a polyfunctional (meth)acrylate monomer and a polyfunctional (meth)acrylate oligomer.

[0159] The mass ratio of the polyfunctional (meth)acrylate monomer to the polyfunctional (meth)acrylate oligomer is preferably 5:95 to 60:40, more preferably 20:80 to 60:40, and even more preferably 40:60 to 60:40.

[0160] By making the polyfunctional (meth)acrylate monomer into a predetermined ratio or more, the scratch resistance of the anti-glare layer can be easily improved.

[0161] By making the multifunctional (meth) acrylate oligomer more than the prescribed ratio, the viscosity of the anti-glare layer coating solution can be increased, the particles can be easily suppressed from sinking to the bottom of the anti-glare layer, and the binder resin can be easily suppressed from flowing down between the convex portions based on the particles. Therefore, Vmp and Sal can be easily adjusted to the above-mentioned range. On the other hand, if the proportion of the multifunctional (meth) acrylate oligomer is too much, the strength of the anti-glare layer can be reduced sometimes. In addition, if the viscosity of the anti-glare layer coating solution is too high, Vmp can become too large or Sal can become too small sometimes. Therefore, the ionizing radiation curable resin composition preferably includes a prescribed amount of multifunctional (meth) acrylate oligomer and a prescribed amount of multifunctional (meth) acrylate monomer.

[0162] The anti-glare layer coating solution preferably contains a solvent in order to adjust the viscosity or dissolve or disperse the components. The surface shape of the anti-glare layer after coating and drying varies depending on the type of solvent, so it is preferred to select the solvent in consideration of the saturated vapor pressure of the solvent, the permeability of the solvent to the substrate, etc.

[0163] Specifically, as for the solvent, for example, ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone (MIBK), cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (isopropyl alcohol, butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), glycol ethers (propylene glycol monomethyl ether acetate, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), amides (dimethylformamide, dimethylacetamide, etc.), etc., and mixtures thereof may also be mentioned.

[0164] The solvent in the anti-glare layer coating solution preferably uses a solvent with a fast evaporation rate as the main component. By accelerating the evaporation rate of the solvent, it is possible to suppress the particles from sinking into the bottom of the anti-glare layer, and then easily suppress the binder resin from flowing down between the convex portions based on the particles. Therefore, Vmp and Sal can be easily adjusted to the above-mentioned range.

[0165] The main component refers to 50% by mass or more of the total amount of the solvent, preferably 70% by mass or more, more preferably 90% by mass or more, and further preferably 97% by mass or more.

[0166] In the present specification, a solvent having a high evaporation rate refers to a solvent having an evaporation rate of 100 or more when the evaporation rate of butyl acetate is 100. The evaporation rate of the solvent having a high evaporation rate is more preferably 120 or more and 300 or less, and further preferably 150 or more and 220 or less.

[0167] Examples of solvents having a fast evaporation rate include methyl isobutyl ketone (evaporation rate: 160), toluene (evaporation rate: 200), and methyl ethyl ketone (evaporation rate: 370).

[0168] On the other hand, examples of the slow evaporation rate solvent having an evaporation rate of less than 100 include cyclohexanone (evaporation rate: 32) and propylene glycol monomethyl ether acetate (evaporation rate: 44).

[0169] When the anti-glare layer is formed from the anti-glare layer coating liquid, it is preferable to control the drying conditions.

[0170] The drying conditions can be controlled by the drying temperature and the wind speed in the dryer. The drying temperature is preferably 30° C. to 120° C., and the drying wind speed is preferably 0.2 m / s to 50 m / s. In addition, in order to control the surface shape of the anti-glare layer by drying, it is preferred to irradiate the coating liquid with ionizing radiation after drying.

[0171] About drying conditions, preferably implement 2 stages of drying within the above-mentioned temperature range and wind speed range. And, preferably, compared with the drying in the first stage, in the drying in the second stage, make the drying temperature high temperature and make the wind speed enhanced. By slowly drying in the first stage, thus, when the binder resin covers the surface of the amorphous inorganic particles, the shape of the amorphous inorganic particles can be easily reflected on the surface of the binder resin. In addition, by making the drying temperature in the second stage higher than the drying temperature in the first stage and enhancing the wind speed, the agglomeration of organic particles can be easily suppressed. Therefore, by carrying out the drying in 2 stages, Vmp and Sal can be easily made into the above-mentioned range.

[0172] In the first stage of drying, the drying temperature is preferably set to 30°C or more and less than 60°C, and the drying wind speed is preferably set to 0.2 m / s or more and less than 7 m / s. In the second stage of drying, the drying temperature is preferably set to 60°C or more and 120°C or less, and the drying wind speed is preferably set to 7 m / s or more and 50 m / s or less.

[0173] Anti-reflective layer

[0174] In order to further improve the anti-glare property, the functional layer preferably has an antireflection layer.

[0175] The surface of the antireflection layer is preferably the concavoconvex surface of the optical film.

[0176] For the anti-reflection layer, for example, a single-layer structure with a low refractive index layer, a two-layer structure with a high refractive index layer and a low refractive index layer, and a multilayer structure with three or more layers can be listed. The low refractive index layer and the high refractive index layer can be formed by a common wet method or a dry method. In the case of a wet method, the single-layer structure or the two-layer structure is preferred, and in the case of a dry method, the multilayer structure is preferred.

[0177] The wet method is superior to the dry method in terms of production efficiency and chemical resistance.

[0178] - Single-layer or two-layer structure -

[0179] The single-layer structure is a single layer of a low-refractive index layer, and the two-layer structure is formed of a high-refractive index layer and a low-refractive index layer. The single-layer structure or the two-layer structure is preferably formed by a wet method.

[0180] Examples of methods for forming an antireflection layer by a wet process include: a method of forming the antireflection layer by a sol-gel method using a metal alkoxide or the like; a method of forming the antireflection layer by coating a low-refractive-index resin such as a fluororesin; and a method of forming the antireflection layer by coating a coating liquid containing low-refractive-index particles or high-refractive-index particles in a binder resin composition.

[0181] In the wet method, in order to improve the close adhesion and scratch resistance, it is also preferred to form the anti-reflection layer by using a coating solution containing low-refractive index particles or high-refractive index particles in the binder resin composition. That is, the low-refractive index layer preferably contains a binder resin and low-refractive index particles. In addition, the high-refractive index layer preferably contains a binder resin and high-refractive index particles.

[0182] The low refractive index layer is preferably disposed on the outermost surface of the optical film.

[0183] When providing antifouling properties to the low refractive index layer, it is preferred that the low refractive index layer contain an antifouling agent such as a silicone compound or a fluorine compound.

[0184] The lower limit of the refractive index of the low refractive index layer is preferably 1.10 or more, more preferably 1.20 or more, more preferably 1.26 or more, more preferably 1.28 or more, more preferably 1.30 or more, and the upper limit is preferably 1.48 or less, more preferably 1.45 or less, more preferably 1.40 or less, more preferably 1.38 or less, more preferably 1.32 or less.

[0185] In this specification, the refractive index refers to a value at a wavelength of 550 nm.

[0186] The lower limit of the thickness of the low refractive index layer is preferably 80 nm or more, more preferably 85 nm or more, more preferably 90 nm or more, and the upper limit is preferably 150 nm or less, more preferably 110 nm or less, more preferably 105 nm or less.

[0187] In order to improve the scratch resistance, the binder resin of the low refractive index layer preferably contains a cured product of a curable resin composition such as a cured product of a thermosetting resin composition or a cured product of an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.

[0188] The binder resin of the low refractive index layer may contain a thermoplastic resin within a range not hindering the effects of the present disclosure.

[0189] Examples of the cured product of the curable resin composition of the low refractive index layer include the same cured products as those exemplified for the cured products of the curable resin composition in the anti-glare layer.

[0190] The ratio of the cured product of the curable resin composition to the total amount of the binder resin in the low refractive index layer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 97% by mass or more.

[0191] The binder resin of the low refractive index layer may also include a thermoplastic resin. By including a thermoplastic resin as the binder resin, the viscosity of the low refractive index layer coating solution can be increased, and the low refractive index layer coating solution is not easy to flow down between the convex portions of the anti-glare layer. That is, by including a thermoplastic resin as the binder resin, even if a low refractive index layer is formed on the anti-glare layer, the surface shape of the anti-glare layer is easily maintained, so Vmp and Sal can be easily adjusted to the above-mentioned range. On the other hand, if the viscosity of the low refractive index layer coating solution is too high, there is the following situation: Vmp becomes too large, or Sal becomes too small.

[0192] For the above-mentioned effects and coating film strength, the content of the thermoplastic resin is preferably 0.1 mass % to 3.0 mass % of the total amount of the binder resin, more preferably 0.2 mass % to 1.5 mass % and even more preferably 0.3 mass % to 0.7 mass %.

[0193] Examples of the thermoplastic resin include polystyrene resins, polyolefin resins, ABS resins (including heat-resistant ABS resins), AS resins, AN resins, polyphenylene ether resins, polycarbonate resins, polyacetal resins, acrylic resins, polyethylene terephthalate resins, polybutylene terephthalate resins, polysulfone resins, and polyphenylene sulfide resins. From the viewpoint of transparency, acrylic resins are preferred.

[0194] The weight average molecular weight of the thermoplastic resin is preferably 20,000 to 200,000, more preferably 30,000 to 150,000, and even more preferably 50,000 to 100,000.

[0195] About low-refractive index particles, hollow particles and solid particles can be listed. As low-refractive index particles, only any one of hollow particles and solid particles can be included, but preferably hollow particles and solid particles are included. By including hollow particles and solid particles, thus, the reduction of coating strength can be suppressed, and the refractive index of low-refractive index layer can be easily and appropriately reduced simultaneously. In the case of preferentially reducing the refractive index of low-refractive index layer, as low-refractive index particles, it is possible to be set to an embodiment comprising hollow particles and not comprising solid particles.

[0196] The material of the hollow particles and the solid particles may be any of inorganic compounds such as silicon dioxide and magnesium fluoride, and organic compounds, but silicon dioxide is preferred for lowering the refractive index and increasing the strength.

[0197] The average primary particle size of the hollow particles is preferably less than the thickness of the low refractive index layer, and for example, 1 nm or more and 150 nm or less can be cited. The average primary particle size of the hollow particles is preferably 35 nm or more and 100 nm or less, more preferably 50 nm or more and 100 nm or less, and further preferably 60 nm or more and 80 nm or less.

[0198] The average primary particle size of the solid particles is preferably smaller than the thickness of the low refractive index layer, and for example, 0.5 nm or more and 100 nm or less can be cited. The average primary particle size of the solid particles is preferably 1 nm or more and 30 nm or less, more preferably 5 nm or more and 20 nm or less, and further preferably 10 nm or more and 15 nm or less.

[0199] When the average primary particle size of the hollow particles is defined as X and the average primary particle size of the solid particles is defined as Y, Y / X is preferably 0.10 to 0.30, more preferably 0.13 to 0.25, and further preferably 0.15 to 0.20. By making Y / X within the above range, it is easy to evenly arrange the hollow particles and the solid particles, and it is easy to make the scratch resistance good.

[0200] The average primary particle diameter of the hollow particles, the solid particles described below, and the high refractive particles described below is calculated by the following operations (A1) to (A3).

[0201] (A1) The cross section of the optical film is photographed using STEM. The acceleration voltage of STEM is 10 kV to 30 kV, and the magnification is 50,000 to 300,000 times.

[0202] (A2) Ten random particles are extracted from the observed image and the particle size of each particle is calculated. When the cross section of each particle is sandwiched between two random parallel straight lines, the distance between the two straight lines in the combination of the two straight lines that is the largest is taken as the particle size of each particle.

[0203] (A3) The same operation is performed five times on another observation image of the same sample, and the value obtained by the number average of the particle sizes of 50 particles in total is taken as the average primary particle size of the particles.

[0204] The more the content of hollow particles, the higher the filling rate of the hollow particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, the content of hollow particles is preferably 100 parts by mass or more, more preferably 150 parts by mass or more relative to 100 parts by mass of the binder resin.

[0205] On the other hand, if the content of hollow particles is too much, hollow particles are easily damaged or fall off, thereby there is a tendency that the mechanical strength such as the scratch resistance of the low-refractive index layer is reduced. Therefore, the content of hollow particles is preferably less than 300 parts by mass, more preferably less than 250 parts by mass relative to 100 parts by mass of binder resin.

[0206] In order to improve the scratch resistance of the low refractive index layer, the content of the solid particles is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, based on 100 parts by mass of the binder resin.

[0207] On the other hand, if the content of the solid particles is too large, the solid particles tend to aggregate. Therefore, the content of the solid particles is preferably 100 parts by mass or less, and more preferably 60 parts by mass or less, relative to 100 parts by mass of the binder resin.

[0208] When the content of the hollow particles relative to 100 parts by mass of the binder resin is defined as A and the content of the solid particles relative to 100 parts by mass of the binder resin is defined as B, B / A is preferably 0.15 or more and 0.40 or less, more preferably 0.17 or more and 0.35 or less, and further preferably 0.20 or more and 0.30 or less. By making B / A within the above range, it is easy to evenly arrange the hollow particles and the solid particles, and it is easy to make the scratch resistance good.

[0209] The high refractive index layer is preferably arranged closer to the anti-glare layer than the low refractive index layer.

[0210] The lower limit of the refractive index of the high refractive index layer is preferably 1.53 or more, more preferably 1.54 or more, more preferably 1.55 or more, more preferably 1.56 or more, and the upper limit is preferably 1.85 or less, more preferably 1.80 or less, more preferably 1.75 or less, more preferably 1.70 or less.

[0211] The upper limit of the thickness of the high refractive index layer is preferably 200 nm or less, more preferably 180 nm or less, further preferably 150 nm or less, and the lower limit is preferably 50 nm or more, more preferably 70 nm or more.

[0212] Examples of the binder resin for the high refractive index layer include the same binder resins as those for the low refractive index layer.

[0213] Examples of the high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide.

[0214] The average primary particle size of the high refractive index particles is preferably more than 2nm, more preferably more than 5nm, and further preferably more than 10nm. In addition, from the viewpoint of suppressing whitening and improving transparency, the average primary particle size of the high refractive index particles is preferably less than 200nm, more preferably less than 100nm, more preferably less than 80nm, more preferably less than 60nm, and more preferably less than 30nm.

[0215] The content of the high refractive index particles may be such that the refractive index of the high refractive index layer falls within the above-mentioned range.

[0216] In the case of forming an anti-reflection layer such as a low refractive index layer and a high refractive index layer by a wet method, it is preferred to increase the viscosity of the anti-reflection layer coating liquid. By increasing the viscosity of the anti-reflection layer coating liquid, the anti-reflection layer coating liquid is not easy to flow down between the convex parts of the anti-glare layer, so even if the anti-reflection layer is formed on the anti-glare layer, the surface shape of the anti-glare layer can be easily maintained. Therefore, by appropriately increasing the viscosity of the anti-reflection layer coating liquid, Vmp and Sal can be easily adjusted to the above range. For example, by adding a thermoplastic resin as a binder resin, or increasing the proportion of an oligomer as an ionizing radiation curable resin composition, or selecting a solvent with a high viscosity as a solvent, etc., the viscosity of the anti-reflection layer coating liquid can be increased.

[0217] On the other hand, if the viscosity of the antireflection layer coating liquid is too high, defects may occur when the antireflection layer coating liquid is applied on the surface of the antiglare layer.

[0218] Therefore, the viscosity of the antireflection layer coating liquid at 23° C. is preferably 0.1 mPa·s or more and 5.0 mPa·s or less.

[0219] Examples of the solvent of the antireflection layer coating liquid include the same solvents as those exemplified as the solvent of the antiglare layer coating liquid.

[0220] When forming the anti-glare layer from the anti-reflection layer coating liquid, it is preferable to control the drying conditions.

[0221] The drying conditions can be controlled by the drying temperature and the wind speed in the dryer. The drying temperature is preferably above 30°C and below 70°C, and the drying wind speed is preferably above 10m / s and below 30m / s. By setting the drying temperature to a low temperature, the viscosity of the anti-reflection layer coating liquid can be easily increased. In addition, by increasing the wind speed, the viscosity of the anti-reflection layer coating liquid can be quickly increased. Therefore, by drying the anti-reflection layer coating liquid at a relatively low temperature and a relatively strong wind speed, the surface shape of the anti-glare layer can be easily maintained. That is, by drying the anti-reflection layer coating liquid at a relatively low temperature and a relatively strong wind speed, Vmp and Sal can be easily controlled.

[0222] It is preferred that the irradiation with ionizing radiation is performed after the antireflection layer coating liquid is dried.

[0223] - In the case of a multi-layer structure with more than 3 layers -

[0224] The multilayer structure preferably formed by the dry method is a structure in which high refractive index layers and low refractive index layers are alternately stacked to form a total of three or more layers. In the multilayer structure, the low refractive index layer is preferably disposed on the outermost surface of the optical film.

[0225] The high refractive index layer preferably has a thickness of 10 nm to 200 nm, and a refractive index of 2.10 to 2.40. The high refractive index layer more preferably has a thickness of 20 nm to 70 nm.

[0226] The low refractive index layer preferably has a thickness of 5 nm to 200 nm, and a refractive index of 1.33 to 1.53. The thickness of the low refractive index layer is more preferably 20 nm to 120 nm.

[0227] <Optical properties>

[0228] The total light transmittance of the optical film in accordance with JIS K7361-1:1997 is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more.

[0229] The light incident surface when measuring the total light transmittance and the haze is the surface on the opposite side to the concavo-convex surface.

[0230] The haze of the optical film in JIS K7136:2000 is preferably 20% to 75%. The lower limit of the haze is more preferably 30% or more, further preferably 40% or more, further preferably 50% or more, and the upper limit is more preferably 70% or less, further preferably 65% ​​or less.

[0231] By setting the haze to 20% or more, the anti-glare property can be easily improved, and by setting the haze to 75% or less, the reduction in the resolution of the image can be easily suppressed.

[0232] Regarding the implementation methods of the haze of the optical film, there can be listed more than 20% and less than 75%, more than 20% and less than 70%, more than 20% and less than 65%, more than 30% and less than 75%, more than 30% and less than 70%, more than 30% and less than 65%, more than 40% and less than 75%, more than 40% and less than 70%, more than 40% and less than 65%, more than 50% and less than 75%, more than 50% and less than 70%, and more than 50% and less than 65%.

[0233] In order to easily improve the resolution and contrast of an image, the internal haze of the optical film is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less.

[0234] Internal haze can be measured by a common method, for example, by laminating a transparent sheet or the like on the concavo-convex surface via a transparent adhesive layer and crushing the concavo-convex surface. The difference between the refractive index of the adhesive of the transparent adhesive layer and the refractive index of the binder resin is 0.05 or less.

[0235] Regarding the transmission image clarity of optical films measured in accordance with JIS K7374:2007, the transmission image clarity when the width of the optical comb is 0.125 mm is defined as C 0.125 , the clarity of the transmitted image with a comb width of 0.25 mm is defined as C 0.25 , the clarity of the transmitted image with a comb width of 0.5 mm is defined as C 0.5 , the clarity of the transmitted image with a comb width of 1.0 mm is defined as C 1.0 , the transmission image clarity with a comb width of 2.0 mm is defined as C 2.0 When C 0.125 , C 0.25 , C 0.5 , C 1.0 and C 2.0 The value of is preferably in the range described below.

[0236] In order to achieve good anti-glare performance, C 0.125 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 0.125 It is preferably 1.0% or more. 0.125 The range of can be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, 1.0% to 20%.

[0237] In order to achieve good anti-glare performance, C 0.25 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 0.25 It is preferably 1.0% or more. 0.25 The range of can be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, 1.0% to 20%.

[0238] In order to achieve good anti-glare performance, C 0.5It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 0.5 It is preferably 1.0% or more. 0.5 The range of can be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, 1.0% to 20%.

[0239] In order to achieve good anti-glare performance, C 1.0 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 1.0 It is preferably 1.0% or more. 1.0 The range of can be 1.0% to 50%, 1.0% to 40%, 1.0% to 30%, 1.0% to 20%.

[0240] In order to achieve good anti-glare performance, C 2.0 It is preferably 50% or less, more preferably 40% or less, more preferably 30% or less, and more preferably 20% or less. 2.0 It is preferably 5.0% or more. 2.0 The range of can be 5.0% to 50%, 5.0% to 40%, 5.0% to 30%, 5.0% to 20%.

[0241] Regarding optical films, in order to achieve good anti-glare properties, C 0.125 , C 0.5 , C 1.0 and C 2.0 The total is preferably 200% or less, more preferably 150% or less, more preferably 100% or less, and more preferably 80% or less. In order to achieve good resolution, the total is preferably 10.0% or more. As the range of the total, 10.0% or more and 200% or less, 10.0% or more and 150% or less, 10.0% or more and 100% or less, and 10.0% or more and 80% or less can be listed.

[0242] <Size, shape, etc.>

[0243] The optical film may be in the form of a single sheet cut into a predetermined size, or in the form of a roll in which a long sheet is rolled up. The size of the single sheet is not particularly limited, but the maximum diameter is about 2 inches or more and 500 inches or less. The "maximum diameter" refers to the maximum length when any two points of the optical film are connected. For example, when the optical film is rectangular, the diagonal of the area becomes the maximum diameter. When the optical film is circular, the diameter of the circle becomes the maximum diameter.

[0244] The width and length of the roll are not particularly limited, but generally speaking, the width is 500 mm or more and 3000 mm or less, and the length is about 500 m or more and 5000 m or less. The optical film in a roll form can be cut into a single piece for use according to the size of the image display device, etc. When cutting, it is preferred to remove the end of the roll with unstable physical properties.

[0245] The shape of the single piece is not particularly limited, and for example, polygons such as triangles, quadrilaterals, and pentagons, circles, random amorphous shapes, etc. can be listed. More specifically, when the optical film is a quadrilateral, the aspect ratio is not particularly limited as long as there is no problem as a display screen. For example, horizontal:vertical = 1:1, 4:3, 16:10, 16:9, 2:1, etc. can be listed, but in the design-rich vehicle-mounted use or digital signage use, it is not limited to such an aspect ratio.

[0246] The surface shape of the optical film opposite to the concavoconvex surface is not particularly limited, but is preferably substantially smooth. Substantially smooth means that the arithmetic mean roughness Ra of JIS B0601:1994 at a cutoff value of 0.8 mm is less than 0.03 μm, preferably 0.02 μm or less.

[0247] The optical film of the present disclosure can be suitably used as an optical component on the light emitting surface side of a display element, and can be suitably used as an optical component disposed on the outermost surface of an image display panel or an image display device.

[0248] [Image Display Panel]

[0249] The image display panel of the present disclosure is configured on a display element in such a manner that the surface of the optical film of the present disclosure on the concavo-convex surface side faces the opposite side of the display element, and the optical film is configured on the outermost surface (refer to Figure 2 ).

[0250] As display elements, liquid crystal display elements, EL display elements (organic EL display elements, inorganic EL display elements), plasma display elements, etc. can be listed, and LED display elements such as micro LED display elements can also be listed. These display elements may also have a touch panel function inside the display element.

[0251] As the display mode of the liquid crystal of the liquid crystal display element, IPS mode, VA mode, multi-domain mode, OCB mode, STN mode, TSTN mode, etc. can be listed. In the case where the display element is a liquid crystal display element, a backlight is required. The backlight is arranged on the side of the liquid crystal display element opposite to the side where the optical film is arranged.

[0252] In addition, the image display panel of the present disclosure may also be an image display panel with a touch panel having a touch panel between the display element and the optical film. In this case, the optical film can be arranged on the outermost surface of the image display panel with a touch panel, and the surface of the concave-convex surface of the optical film is arranged in a manner facing the side opposite to the display element.

[0253] The size of the image display panel is not particularly limited, but the maximum diameter is about 2 inches or more and 500 inches or less. The maximum diameter refers to the maximum length when connecting any two points in the plane of the image display panel.

[0254] [Image display device]

[0255] The image display device of the present disclosure includes the image display panel of the present disclosure.

[0256] In the image display device, the optical film is arranged on the outermost surface of the image display device.

[0257] The image display device of the present disclosure preferably further includes: a drive control unit electrically connected to the image display panel; and a housing that accommodates the image display panel, the drive control unit, and the like.

[0258] When the display element is a liquid crystal display element, a backlight is required in the image display device of the present disclosure. The backlight is arranged on the side of the liquid crystal display element opposite to the light emitting surface side.

[0259] The size of the image display device is not particularly limited, but the maximum diameter of the effective display area is approximately not less than 2 inches and not more than 500 inches.

[0260] The effective display area of ​​an image display device refers to an area where an image can be displayed. For example, when the image display device has a casing surrounding a display element, the area inside the casing becomes the effective image area.

[0261] In addition, the maximum diameter of the effective image area refers to the maximum length when connecting any two points in the effective image area. For example, when the effective image area is a rectangle, the diagonal of the area becomes the maximum diameter. In addition, when the effective image area is a circle, the diameter of the area becomes the maximum diameter.

[0262] The present disclosure includes the following [1] to

[14] .

[0263] [1] An optical film, wherein:

[0264] The optical film has a concavoconvex surface,

[0265] Regarding the concave-convex surface, the protruding peak solid volume Vmp specified by ISO 25178-2:2012 is 0.010 ml / m 2 Above and 0.050ml / m 2 Hereinafter, the minimum autocorrelation length Sal prescribed by ISO 25178-2:2012 is 4.0 μm or more and 12.0 μm or less.

[0266] [2] The optical film according to [1], wherein, with respect to the concavo-convex surface, the core space volume Vvc specified by ISO 25178-2:2012 is 0.30 ml / m 2 Above and 1.00ml / m 2 the following.

[0267] [3] The optical film according to [1] or [2], wherein the peak height Sxp specified in ISO 25178-2:2012 on the concavoconvex surface is 0.55 μm or more and 2.00 μm or less.

[0268] [4] The optical film according to any one of [1] to [3], wherein the arithmetic mean height Sa specified in ISO 25178-2:2012 on the concavo-convex surface is 0.20 μm or more and 1.00 μm or less.

[0269] [5] The optical film according to any one of [1] to [4], wherein the optical film has a functional layer on a substrate, and a surface of the functional layer is the concavo-convex surface.

[0270] [6] The optical film according to [5], wherein the optical film includes an anti-glare layer as the functional layer, and a surface of the anti-glare layer is the concavo-convex surface.

[0271] [7] The optical film according to [5], wherein the optical film includes an anti-glare layer and an anti-reflection layer as the functional layer, and a surface of the anti-reflection layer is the concavo-convex surface.

[0272] [8] The optical film according to [6] or [7], wherein the anti-glare layer contains a binder resin and particles.

[0273] [9] The optical film according to [8], wherein the optical film contains amorphous inorganic particles as the particles.

[0274]

[10] The optical film according to [9], further comprising organic particles as the particles.

[0275]

[11] The optical film according to any one of [8] to

[10] , wherein the binder resin includes a cured product of an ionizing radiation-curable resin composition.

[0276]

[12] The optical film according to any one of [1] to

[11] , wherein the haze according to JIS K7136:2000 is 20% or more and 75% or less.

[0277]

[13] An image display panel, wherein the image display panel is arranged on a display element in such a manner that the surface of the concave-convex surface side of the optical film described in any one of [1] to

[12] faces the side opposite to the display element, and the optical film is arranged on the outermost surface.

[0278]

[13] An image display device, comprising the image display panel described in

[12] .

[0279] Example

[0280] Next, the present disclosure will be described in more detail by way of examples, but the present disclosure is not limited to these examples at all. In addition, "parts" and "%" are based on mass unless otherwise specified.

[0281] 1. Measurement and evaluation

[0282] The optical films of the embodiments and comparative examples were measured and evaluated as follows. The atmosphere during each measurement and evaluation was: the temperature was 23±5°C, and the relative humidity was 40% to 65%. In addition, before each measurement and evaluation, the target sample was exposed to the atmosphere for 30 minutes to 60 minutes, and then the measurement and evaluation were performed. The results are shown in Table 1 or 2.

[0283] 1-1. Measurement of surface shape

[0284] The anti-glare films of the examples and comparative examples were cut into 10 cm × 10 cm. The cut portion was selected from random locations after visually confirming that there were no abnormalities such as dirt and scratches. Sample 1 was prepared as follows: the substrate side of the cut anti-glare film was bonded to a glass plate (thickness 2.0 mm) of 10 cm × 10 cm in length with the aid of an optically transparent adhesive sheet (trade name: Panaclean PD-S1, thickness 25 μm) from PANAC.

[0285] Using a confocal laser microscope (VK-X250 (control unit), VK-X260 (measurement unit)), after setting the sample 1 in a fixed and close-fitting state on the measurement table, the surface shape of the anti-glare film was measured and analyzed under the following measurement condition 1, image processing condition 1, and analysis condition 1. In addition, as the measurement / analysis software, a multi-file analysis application (version 1.3.1.120) was used. The surface shape was measured in an environment without vibration (the surface shape can also be measured in an environment where vibration is suppressed, such as using an anti-vibration table).

[0286] (Measurement condition 1)

[0287] Laser wavelength: 408nm

[0288] Optical system for measurement: Confocal optical system

[0289] Objective lens: 150 times

[0290] Zoom: 1x

[0291] Measuring area: 93.95μm×70.44μm

[0292] Number of measurement points: 1024×768 points

[0293] Measurement conditions: Transparent surface shape / high precision / double scanning

[0294] (Image processing condition 1)

[0295] DCL / BCL: DCL=13000, BCL=65535, processing method: supplement from surrounding pixels

[0296] Height cut-off level: Strong

[0297] (Analysis condition 1)

[0298] Region: The entire region

[0299] Filter type: Gaussian

[0300] S-filter: 0.25μm

[0301] F-operation: plane tilt correction (area designation)

[0302] L-filter: None

[0303] Terminal effect correction: ON

[0304] p and q when calculating Sxp: p = 2.5%; q = 50.0%

[0305] · s when calculating Sal: s = 0.20

[0306] "Vmp", "Sal", "Vvc", "Sxp", and "Sa" of each measurement area are displayed from the analysis software and are used as measurement values.

[0307] 1-2. Haze (Hz)

[0308] The optical films of the examples and comparative examples were cut into 10 cm squares. The cut parts were selected from random parts after visually confirming that there were no abnormal points such as dirt and scratches. The haze of each sample according to JIS K7136:2000 was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory).

[0309] After turning on the power switch of the device in advance so that the light source is stable, wait for 15 minutes or more, perform calibration without placing anything at the entrance opening, and then place the measurement sample at the entrance opening for measurement. The light incident surface is the substrate side.

[0310] Furthermore, the total light transmittance of the optical films of Examples and Comparative Examples was 90% or more.

[0311] 1-3. Transmitted image clarity

[0312] The optical films of the embodiments and comparative examples were cut into 10 cm squares. The cut parts were selected from random locations after visually confirming that there were no abnormalities such as dirt and scratches. The image clarity of the sample was measured using an imaging meter (trade name: ICM-1T) manufactured by Suga Testing Instruments Co., Ltd. in accordance with JIS K7374:2007. The width of the optical comb was 5: 0.125 mm, 0.25 mm, 0.5 mm, 1.0 mm, and 2.0 mm. The light incident surface during measurement was set to the transparent substrate side. C 0.125 , C 0.25 , C 0.5 , C 1.0 and C 2.0 The value of C 0.125 , C 0.5 , C 1.0 and C 2.0 The total values ​​are shown in Table 2.

[0313] 1-4. Anti-glare

[0314] The optical films of the embodiments and comparative examples were cut into 10 cm × 10 cm. The cut portion was selected from random locations after visually confirming that there were no abnormalities such as dirt and scratches. Sample 2 was produced as follows: the substrate side of the cut anti-glare film was bonded to a black plate (Kuraray, trade name: Comoglass DFA2CG 502K (black), thickness 2 mm) with a size of 10 cm × 10 cm using an optically transparent adhesive sheet (trade name: Panaclean PD-S1) from PANAC.

[0315] In a bright room environment, the sample 2 was placed on a horizontal platform at a height of 70 cm with the concavo-convex surface facing upward. At this time, the sample was placed approximately directly below the illumination light. The sample was observed from the front (where the observer did not block the illumination light), and the reflection of the illumination light on the concavo-convex surface was evaluated according to the following evaluation criteria.

[0316] For lighting, a straight tube three-wavelength daylight fluorescent lamp of type Hf32 was used, and the lighting position was set at a height of 2m above the horizontal platform in the vertical direction. The evaluation was performed within the range of illuminance of 500 lux or more and 1000 lux or less on the concave and convex surface of the sample. The observer's line of sight was about 120cm from the ground. The observer was a healthy person in his 30s with a visual acuity of 0.7 or more.

[0317] <Evaluation Criteria>

[0318] A: There is no outline of the lighting and the location is unknown

[0319] B: Although there is no lighting outline, the location is vaguely known

[0320] C: The outline and position of the lighting can be vaguely seen

[0321] D: The outline of the lighting is clearer and the position is also clear

[0322] 1-5. Darkness

[0323] As the sample, sample 2 prepared in 1-4 was used. The sample was observed in the same manner as in 1-4 except that the observer's line of sight was changed to about 160 cm above the ground.

[0324] 20 subjects evaluated based on the following evaluation points. There were 5 subjects in each age group from 20 to 50. The average score of the evaluation of the 20 people was calculated and ranked according to the following criteria.

[0325] <Evaluation score>

[0326] (1) Not feeling white but feeling black: 3 points

[0327] (2) Although it is black, it feels slightly white: 2 points

[0328] (3) Notice white: 1 point

[0329] <Evaluation Criteria>

[0330] A: Average score is 2.5 or above

[0331] B: Average score is 2.0 or more and less than 2.5

[0332] C: Average score is 1.5 or more and less than 2.0

[0333] D: Average score less than 1.5

[0334] 1-6. Scratch resistance

[0335] As for the sample, sample 2 prepared in 1-4 was used. For sample 2, it was attached to the base of the Gakushin wear tester (manufactured by TESTER SANGYO Co., Ltd., with the product name "AB-301") so that the concave and convex surface became the upper surface. Steel wool #0000 (manufactured by Nippon Steel Wool Co., Ltd., with the product name "BONSTAR B-204") was set. The steel wool was brought into contact with the concave and convex surface, and the steel wool was reciprocated 10 times while applying a load at a moving speed of 100 mm / sec and a reciprocating moving distance of 200 mm. The contact area between the steel wool and the sample was set to 1 cm 2 .

[0336] Then, each sample was visually observed under fluorescent light to check the number of scratches. At this time, the illumination on the sample was 800 lux or more and 1200 lux or less, and the observation distance was 30 cm.

[0337] For each sample, the maximum load per unit area (g / cm2) at which no scratches were observed after the test was confirmed. 2 ) For each sample, the test was performed with n=2, the average value of the maximum load was calculated, and the evaluation was performed according to the following criteria.

[0338] <Evaluation Criteria>

[0339] A: Maximum load is 300g / cm 2 above

[0340] B: Maximum load is 200g / cm 2 Above and less than 300g / cm 2

[0341] C: Maximum load less than 200g / cm 2

[0342] 1-7. Comprehensive evaluation

[0343] Comprehensive evaluation was performed based on the following criteria based on the three evaluations of anti-glare property, black feeling, and scratch resistance.

[0344] <Evaluation Criteria>

[0345] A: All 3 ratings are A.

[0346] B: Out of 3 evaluations, 2 were A and 1 was B.

[0347] C: All three ratings were B. Or, two of the three ratings were B and one was A.

[0348] D: Only one of the three ratings must be C or D.

[0349] 2. Production of optical films

[0350] [Example 1]

[0351] The following anti-glare coating liquid 1 was applied on a substrate (triacetyl cellulose resin film with a thickness of 80 μm, Fujifilm Corporation, TD80UL). Then, it was dried at 50°C and a wind speed of 5 m / s for 30 seconds, and further dried at 70°C and a wind speed of 10 m / s for 45 seconds. Then, it was dried in a nitrogen atmosphere with an oxygen concentration of 200 ppm or less at a cumulative light intensity of 50 mJ / cm 2 The anti-glare layer with a thickness of 5.8 μm was formed by irradiating ultraviolet rays in a manner.

[0352] Next, the anti-glare layer was coated with the following low refractive index layer coating solution. Next, it was dried at 50°C and a wind speed of 20 m / s for 30 seconds. Next, it was heated in a nitrogen atmosphere with an oxygen concentration of 200 ppm or less at a cumulative light intensity of 150 mJ / cm 2 The ultraviolet rays were irradiated in a manner to form a low refractive index layer with a thickness of 0.10 μm, thereby obtaining an optical film of Example 1. The refractive index of the low refractive index layer was 1.31.

[0353] The anti-glare layers of Examples 1 to 8 and Comparative Examples 1 to 4 were produced by the method (d1) in the main text of the specification.

[0354] <Anti-glare layer coating liquid 1>

[0355] Polyurethane acrylate A 35 parts

[0356] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0357] · Polyurethane acrylate B 15 parts

[0358] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0359] · Pentaerythritol triacrylate 50 parts

[0360] (Toa Gosei Co., Ltd., trade name: M-305)

[0361] · 25 parts of silicon dioxide particles

[0362] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0363] · Organic particles A 9 parts

[0364] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0365] · Photopolymerization initiator 4.0 parts

[0366] (IGM Resins BV, trade name: Omnirad184)

[0367] ·0.6 parts of photopolymerization initiator

[0368] (IGM Resins BV, trade name: Omnirad907)

[0369] 0.1 part of silicone leveling agent

[0370] (Momentive Performance Materials, trade name: TSF 4460)

[0371] Solvent (toluene) 180.4 parts

[0372] Solvent (cyclohexanone) 4.0 parts

[0373] Solvent (methyl isobutyl ketone) 49.4 parts

[0374] <Low refractive index layer coating liquid>

[0375] ·100 parts of multifunctional acrylate composition

[0376] (Manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd., trade name "New Frontier MF-001")

[0377] ·Acrylic acid polymer 0.5 parts

[0378] (Weight average molecular weight: 55000)

[0379] ·200 parts of hollow silica particles

[0380] (Average primary particle size 75 nm, particles surface treated with a silane coupling agent having a methacryloyl group)

[0381] ·50 parts of solid silicon dioxide particles

[0382] (Average primary particle size of 12.5 nm, particles surface-treated with a silane coupling agent having a methacryloyl group)

[0383] ·15 parts of silicone leveling agent

[0384] (Shin-Etsu Chemical Co., Ltd., trade name "X-22-164E")

[0385] · 4.3 parts of photopolymerization initiator

[0386] (IGM Resins, trade name "Omnirad127")

[0387] Solvent 14867 parts

[0388] (Mixed solvent of methyl isobutyl ketone and 1-methoxy-2-propyl acetate. Mass ratio = 72 / 28)

[0389] [Examples 2 to 8]

[0390] Optical films of Examples 2 to 8 were obtained in the same manner as in Example 1 except that the anti-glare layer coating liquid 1 was changed to the anti-glare layer coating liquids 2 to 8 described below.

[0391] [Example 9]

[0392] The anti-glare coating liquid 9 of the following formulation was applied to a transparent substrate (triacetyl cellulose resin film (TAC) with a thickness of 80 μm, Fujifilm Corporation, TD80UL) and dried at 70° C. and a wind speed of 1 m / s for 60 seconds. The accumulated light intensity was then 60 mJ / cm 2 The anti-glare layer was irradiated in a manner of , thereby forming an anti-glare layer. The thickness of the anti-glare layer was 8.5 μm. Next, a low refractive index layer was formed on the anti-glare layer in the same manner as in Example 1, thereby obtaining an optical film of Example 9.

[0393] [Comparative Example 1]

[0394] An optical film of Comparative Example 1 was obtained in the same manner as in Example 1 except that the anti-glare layer coating liquid 1 was changed to the anti-glare layer coating liquid 10 described below and the thickness of the anti-glare layer was changed to 4.5 μm.

[0395] [Comparative Example 2]

[0396] An optical film of Comparative Example 2 was obtained in the same manner as in Example 1 except that the anti-glare layer coating liquid 1 was changed to the anti-glare layer coating liquid 11 described below and the thickness of the anti-glare layer was changed to 4.4 μm.

[0397] [Comparative Examples 3-4]

[0398] Optical films of Comparative Examples 3 and 4 were obtained in the same manner as in Example 1 except that the anti-glare layer coating liquid 1 was changed to the anti-glare layer coating liquids 12 and 13 described below.

[0399] <Anti-glare layer coating liquid 2>

[0400] Polyurethane acrylate A 35 parts

[0401] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0402] · Polyurethane acrylate B 15 parts

[0403] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0404] · Pentaerythritol triacrylate 50 parts

[0405] (Toa Gosei Co., Ltd., trade name: M-305)

[0406] · 23 parts of silicon dioxide particles

[0407] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0408] · Organic particles A 5.8 parts

[0409] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0410] · Organic particles B 4.3 parts

[0411] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0412] · Photopolymerization initiator 4.1 parts

[0413] (IGM Resins BV, trade name: Omnirad184)

[0414] · Photopolymerization initiator 0.7 parts

[0415] (IGM Resins BV, trade name: Omnirad907)

[0416] 0.1 part of silicone leveling agent

[0417] (Momentive Performance Materials, trade name: TSF 4460)

[0418] Solvent (toluene) 216.0 parts

[0419] Solvent (cyclohexanone) 1.5 parts

[0420] Solvent (methyl isobutyl ketone) 18.9 parts

[0421] <Anti-glare layer coating liquid 3>

[0422] Polyurethane acrylate A 35 parts

[0423] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0424] · Polyurethane acrylate B 15 parts

[0425] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0426] · Pentaerythritol triacrylate 50 parts

[0427] (Toa Gosei Co., Ltd., trade name: M-305)

[0428] · 23 parts of silicon dioxide particles

[0429] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0430] · Organic particles A 4.1 parts

[0431] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0432] Organic particles B 5.9 parts

[0433] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0434] · Photopolymerization initiator 4.1 parts

[0435] (IGM Resins BV, trade name: Omnirad184)

[0436] · Photopolymerization initiator 0.7 parts

[0437] (IGM Resins BV, trade name: Omnirad907)

[0438] 0.1 part of silicone leveling agent

[0439] (Momentive Performance Materials, trade name: TSF 4460)

[0440] Solvent (toluene) 201.2 parts

[0441] Solvent (cyclohexanone) 2.3 parts

[0442] Solvent (methyl isobutyl ketone) 22.5 parts

[0443] <Anti-glare layer coating liquid 4>

[0444] Polyurethane acrylate A 35 parts

[0445] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0446] · Polyurethane acrylate B 15 parts

[0447] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0448] · Pentaerythritol triacrylate 50 parts

[0449] (Toa Gosei Co., Ltd., trade name: M-305)

[0450] · 21 parts of silicon dioxide particles

[0451] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0452] · Organic particles A 4.1 parts

[0453] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0454] Organic particles B 5.9 parts

[0455] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0456] · 3.8 parts of photopolymerization initiator

[0457] (IGM Resins BV, trade name: Omnirad184)

[0458] · Photopolymerization initiator 0.7 parts

[0459] (IGM Resins BV, trade name: Omnirad907)

[0460] 0.2 parts of silicone leveling agent

[0461] (Momentive Performance Materials, trade name: TSF 4460)

[0462] Solvent (toluene) 182.2 parts

[0463] Solvent (cyclohexanone) 1.5 parts

[0464] Solvent (methyl isobutyl ketone) 37.5 parts

[0465] <Anti-glare layer coating liquid 5>

[0466] Polyurethane acrylate A 35 parts

[0467] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0468] · Polyurethane acrylate B 15 parts

[0469] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0470] · Pentaerythritol triacrylate 50 parts

[0471] (Toa Gosei Co., Ltd., trade name: M-305)

[0472] ·Silica particles 19 parts

[0473] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0474] · Organic particles B 12 parts

[0475] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0476] · 3.7 parts of photopolymerization initiator

[0477] (IGM Resins BV, trade name: Omnirad184)

[0478] ·0.6 parts of photopolymerization initiator

[0479] (IGM Resins BV, trade name: Omnirad907)

[0480] 0.2 parts of silicone leveling agent

[0481] (Momentive Performance Materials, trade name: TSF 4460)

[0482] Solvent (toluene) 216.7 parts

[0483] Solvent (cyclohexanone) 2.5 parts

[0484] Solvent (methyl isobutyl ketone) 32.7 parts

[0485] <Anti-glare layer coating liquid 6>

[0486] Polyurethane acrylate A 35 parts

[0487] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0488] · Polyurethane acrylate B 15 parts

[0489] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0490] · Pentaerythritol triacrylate 50 parts

[0491] (Toa Gosei Co., Ltd., trade name: M-305)

[0492] ·Silica particles 19 parts

[0493] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0494] ·Organic particles A 11 parts

[0495] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0496] · Organic particles B 1 part

[0497] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0498] · 3.7 parts of photopolymerization initiator

[0499] (IGM Resins BV, trade name: Omnirad184)

[0500] · Photopolymerization initiator 0.6 parts

[0501] (IGM Resins BV, trade name: Omnirad907)

[0502] 0.2 parts of silicone leveling agent

[0503] (Momentive Performance Materials, trade name: TSF 4460)

[0504] Solvent (toluene) 175.2 parts

[0505] Solvent (cyclohexanone) 4.5 parts

[0506] Solvent (methyl isobutyl ketone) 33.5 parts

[0507] <Anti-glare layer coating liquid 7>

[0508] Polyurethane acrylate A 35 parts

[0509] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0510] · Polyurethane acrylate B 15 parts

[0511] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0512] · Pentaerythritol triacrylate 50 parts

[0513] (Toa Gosei Co., Ltd., trade name: M-305)

[0514] ·Silica particles 17 parts

[0515] (Surface treated amorphous silica, d10: 2.3 μm, d50: 5.1 μm, d90: 7.4 μm)

[0516] ·Organic particles A 11 parts

[0517] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0518] · Organic particles B 1 part

[0519] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0520] · 3.7 parts of photopolymerization initiator

[0521] (IGM Resins BV, trade name: Omnirad184)

[0522] · Photopolymerization initiator 0.6 parts

[0523] (IGM Resins BV, trade name: Omnirad907)

[0524] 0.2 parts of silicone leveling agent

[0525] (Momentive Performance Materials, trade name: TSF 4460)

[0526] Solvent (toluene) 182.1 parts

[0527] Solvent (cyclohexanone) 2.8 parts

[0528] Solvent (methyl isobutyl ketone) 38.3 parts

[0529] <Anti-glare layer coating liquid 8>

[0530] Polyurethane acrylate A 35 parts

[0531] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0532] · Polyurethane acrylate B 15 parts

[0533] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0534] · Pentaerythritol triacrylate 50 parts

[0535] (Toa Gosei Co., Ltd., trade name: M-305)

[0536] ·Silica particles 17 parts

[0537] (Surface treated amorphous silica, d10: 1.4μm, d50: 3.5μm, d90: 6.3μm)

[0538] · Organic particles A 4.1 parts

[0539] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0540] Organic particles B 5.9 parts

[0541] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0542] · 4.2 parts of photopolymerization initiator

[0543] (IGM Resins BV, trade name: Omnirad184)

[0544] ·0.8 parts of photopolymerization initiator

[0545] (IGM Resins BV, trade name: Omnirad907)

[0546] 0.2 parts of silicone leveling agent

[0547] (Momentive Performance Materials, trade name: TSF 4460)

[0548] Solvent (toluene) 203.2 parts

[0549] Solvent (cyclohexanone) 1.7 parts

[0550] Solvent (methyl isobutyl ketone) 25.8 parts

[0551] <Anti-glare layer coating liquid 9>

[0552] ·6.0 parts of oligomer containing isobornyl methacrylate

[0553] · Pentaerythritol triacrylate 20 parts

[0554] (Toa Gosei Co., Ltd., trade name: M-305)

[0555] ·30 parts of dipentaerythritol hexaacrylate

[0556] (Toa Gosei Co., Ltd., trade name: M-402)

[0557] 70 parts of inorganic microparticle dispersion

[0558] (Nissan Chemical Co., Ltd., silica with reactive functional groups introduced on the surface, solvent: MIBK, solid content: 35.5%)

[0559] · 3 parts of photopolymerization initiator

[0560] (IGM Resins BV, trade name: Omnirad184)

[0561] · Photopolymerization initiator 1 part

[0562] (IGM Resins BV, trade name: Omnirad907)

[0563] Solvent (isopropyl alcohol) 100 parts

[0564] <Anti-glare layer coating liquid 10>

[0565] · Pentaerythritol triacrylate 100 parts

[0566] (Toa Gosei Co., Ltd., trade name: M-305)

[0567] ·15 parts of silicon dioxide particles

[0568] (Surface treated amorphous silica, d10: 2.2 μm, d50: 4.0 μm, d90: 6.8 μm)

[0569] · Organic particles C 2 parts

[0570] (Spherical polyacrylic acid-styrene copolymer, average particle size 5.0 μm (the proportion of particles with a particle size of 4.8 to 5.2 μm is 90% or more), refractive index 1.515)

[0571] ·6 parts of photopolymerization initiator

[0572] (IGM Resins BV, trade name: Omnirad184)

[0573] · Photopolymerization initiator 1 part

[0574] (IGM Resins BV, trade name: Omnirad907)

[0575] 0.1 part of silicone leveling agent

[0576] (Momentive Performance Materials, trade name: TSF 4460)

[0577] Solvent (toluene) 170 parts

[0578] Solvent (cyclohexanone) 60 parts

[0579] <Anti-glare layer coating liquid 11>

[0580] · Pentaerythritol triacrylate 90 parts

[0581] (Made in Japan by Nippon Kayaku Co., Ltd., KAYARAD-PET-30)

[0582] ·Acrylic polymer 10 parts

[0583] (Molecular weight 75000)

[0584] ·Organic particles D18 parts

[0585] (Spherical polyacrylic acid-styrene copolymer, average particle size 3.5 μm (the proportion of particles with a particle size of 3.3 to 3.7 μm is 90% or more), refractive index 1.590)

[0586] ·120 parts of inorganic ultrafine particles

[0587] (Silica with reactive functional groups introduced on the surface, solvent is MIBK, solid content is 30%)

[0588] (Average primary particle size: 12nm)

[0589] ·6 parts of photopolymerization initiator

[0590] (IGM Resins BV, trade name: Omnirad184)

[0591] · Photopolymerization initiator 1 part

[0592] (IGM Resins BV, trade name: Omnirad907)

[0593] 0.04 parts of silicone leveling agent

[0594] (Momentive Performance Materials, trade name: TSF 4460)

[0595] Solvent (toluene) 150 parts

[0596] Solvent (cyclohexanone) 75 parts

[0597] <Anti-glare layer coating liquid 12>

[0598] Polyurethane acrylate A 35 parts

[0599] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0600] · Polyurethane acrylate B 15 parts

[0601] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0602] · Pentaerythritol triacrylate 50 parts

[0603] (Toa Gosei Co., Ltd., trade name: M-305)

[0604] ·Silica particles 11.9 parts

[0605] (Surface treated amorphous silica, d10: 1.4μm, d50: 3.5μm, d90: 6.3μm)

[0606] · Organic particles A 4 parts

[0607] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0608] · Organic particles B 6 parts

[0609] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0610] · 3.4 parts of photopolymerization initiator

[0611] (IGM Resins BV, trade name: Omnirad184)

[0612] ·0.8 parts of photopolymerization initiator

[0613] (IGM Resins BV, trade name: Omnirad907)

[0614] 0.2 parts of silicone leveling agent

[0615] (Momentive Performance Materials, trade name: TSF 4460)

[0616] Solvent (toluene) 180.2 parts

[0617] Solvent (cyclohexanone) 2.5 parts

[0618] Solvent (methyl isobutyl ketone) 25.3 parts

[0619] <Anti-glare layer coating liquid 13>

[0620] Polyurethane acrylate A 35 parts

[0621] (Mitsubishi Chemical Corporation, trade name: U-1700B, molecular weight: 2000, number of functional groups: 10)

[0622] · Polyurethane acrylate B 15 parts

[0623] (Shin-Nakamura Chemical Industry Co., Ltd., trade name: U-15HA, molecular weight 2300, number of functional groups 15)

[0624] · Pentaerythritol triacrylate 50 parts

[0625] (Toa Gosei Co., Ltd., trade name: M-305)

[0626] · 20 parts of silicon dioxide particles

[0627] (Surface treated amorphous silica, d10: 0.8 μm, d50: 2.8 μm, d90: 4.5 μm)

[0628] · Organic particles A 4 parts

[0629] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.515)

[0630] ·Organic particles B 10 parts

[0631] (Spherical polyacrylic acid-styrene copolymer, average particle size 1.5 μm (the proportion of particles with a particle size of 1.3 to 1.7 μm is 90% or more), refractive index 1.590)

[0632] · Photopolymerization initiator 4.0 parts

[0633] (IGM Resins BV, trade name: Omnirad184)

[0634] ·0.8 parts of photopolymerization initiator

[0635] (IGM Resins BV, trade name: Omnirad907)

[0636] 0.2 parts of silicone leveling agent

[0637] (Momentive Performance Materials, trade name: TSF 4460)

[0638] Solvent (toluene) 214.6 parts

[0639] Solvent (cyclohexanone) 1.4 parts

[0640] Solvent (methyl isobutyl ketone) 18.4 parts

[0641] In the antiglare layer coating solutions 1 to 13, the urethane acrylates A to B are all urethane acrylate oligomers.

[0642] [Table 1]

[0643] Table 1

[0644]

[0645] [Table 2]

[0646] Play 2

[0647]

[0648] From the results in Table 1, it can be confirmed that the optical films of Examples are excellent in anti-glare properties and scratch resistance.

[0649] The optical film of Comparative Example 1 had a large Vmp and therefore could not satisfy the scratch resistance. The optical film of Comparative Example 2 had a small Vmp and therefore could not satisfy the pitch-black feeling. The optical film of Comparative Example 3 had a large Sal and therefore could not satisfy the pitch-black feeling. The optical film of Comparative Example 4 had a small Sal and therefore could not satisfy the scratch resistance.

[0650] Description of symbols

[0651] 10: Base material

[0652] 20: Functional layer

[0653] 21: Anti-glare layer

[0654] 22: Anti-reflective layer

[0655] 100: Optical film

[0656] 110: Display components

[0657] 120: Image display panel

Claims

1. An optical film, wherein: The optical film has a concavoconvex surface, Regarding the concavoconvex surface, the protruding peak portion solid volume Vmp is 0.010 ml / m2 as specified in ISO 25178-2:2012 when the load area ratio for separating the core portion and the protruding peak portion is set to 10%. 2 Above and 0.050ml / m 2 The minimum autocorrelation length Sal specified in ISO25178-2:2012 is 4.0 μm or more and 12.0 μm or less. The optical film has a functional layer on a substrate, and includes an anti-glare layer as the functional layer, and a surface of the anti-glare layer is the concavo-convex surface.

2. An optical film, wherein: The optical film has a concavoconvex surface, Regarding the concavoconvex surface, the protruding peak portion solid volume Vmp is 0.010 ml / m2 as specified in ISO 25178-2:2012 when the load area ratio for separating the core portion and the protruding peak portion is set to 10%. 2 Above and 0.050ml / m 2 The minimum autocorrelation length Sal specified in ISO25178-2:2012 is 4.0 μm or more and 12.0 μm or less. The optical film has a functional layer on a substrate, and includes an anti-glare layer and an anti-reflection layer as the functional layer, and a surface of the anti-reflection layer is the concavo-convex surface.

3. An optical film, wherein: The optical film has a concavoconvex surface, Regarding the concavoconvex surface, the protruding peak portion solid volume Vmp is 0.010 ml / m2 as specified in ISO 25178-2:2012 when the load area ratio for separating the core portion and the protruding peak portion is set to 10%. 2 Above and 0.050ml / m 2 The minimum autocorrelation length Sal specified in ISO25178-2:2012 is 4.0 μm or more and 12.0 μm or less. The haze of JIS K7136:2000 is 20% or more and 75% or less.

4. The optical film according to any one of claims 1 to 3, wherein: Regarding the concavoconvex surface, the core space volume Vvc when the load area ratio separating the core and the protruding peak is set to 80% as specified in ISO 25178-2:2012 is 0.30 ml / m 2 Above and 1.00ml / m 2 the following.

5. The optical film according to any one of claims 1 to 3, wherein: Regarding the uneven surface, the peak height Sxp specified by ISO 25178-2:2012 is 0.55 μm or more and 2.00 μm or less, wherein the peak height Sxp is the difference between the height at a load area ratio of 2.5% and the height at a load area ratio of 50%.

6. The optical film according to any one of claims 1 to 3, wherein: Regarding the uneven surface, an arithmetic mean height Sa specified by ISO 25178-2:2012 is 0.20 μm or more and 1.00 μm or less.

7. The optical film according to claim 3, wherein: The optical film has a functional layer on a substrate, and a surface of the functional layer is the concavo-convex surface.

8. The optical film according to claim 7, wherein: The optical film includes an anti-glare layer as the functional layer, and a surface of the anti-glare layer is the concavo-convex surface.

9. The optical film according to claim 7, wherein: The optical film includes an anti-glare layer and an anti-reflection layer as the functional layers, and a surface of the anti-reflection layer is the concavo-convex surface.

10. The optical film according to any one of claims 1, 2, 8 and 9, wherein: The anti-glare layer includes a binder resin and particles.

11. The optical film according to claim 10, wherein: The optical film includes amorphous inorganic particles as the particles.

12. The optical film according to claim 11, wherein The optical film further includes organic particles as the particles.

13. The optical film according to claim 10, wherein: The binder resin includes a cured product of an ionizing radiation-curable resin composition.

14. The optical film according to claim 1 or 2, wherein: The haze of JIS K7136:2000 is 20% or more and 75% or less.

15. The optical film according to any one of claims 1 to 3, wherein: The concavo-convex surface is located on the outermost surface of the optical film.

16. An image display panel, wherein: The image display panel is formed on a display element with the concavo-convex surface of the optical film according to any one of claims 1 to 3 disposed on the opposite side to the display element, and the optical film is disposed on the outermost surface.

17. An image display device, wherein: The image display device includes the image display panel according to claim 16.

Citation Information

Patent Citations

  • Anti-glare film

    WO2019026471A1

  • Anti-dazzle film, anti-dazzle polarizer and image display apparatus

    CN101726768A

  • Optical film and manufacturing method therefor, anti-glare film, polarizing element with optical layer, and display device

    CN101815958A